SPECIFIC FEATURES OF IMPROVING BUSINESS PROCESSES IN THE ACTIVITY OF AN INSURANCE ORGANIZATION - Yakubova N.T. (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The basis of the development of business processes of insurance activity is explained in the article, and the nature of the business process in insurance activity is revealed in it.